Optimization of ultrasound image quality via visual servoing - Chatelain, Pierre; Krupa, Alexandre; Navab, Nassir (Proceedings - IEEE International Conference on Robotics and Automation, 2015)
In this paper we propose a new ultrasound-based visual servoing framework, for the optimization of the positioning of an ultrasound probe manipulated by a robotic arm, in order to improve the quality of the acquired ultrasound images. To this end, we use the recent framework of ultrasound confidence map, which aims at estimating the perpixel quality of the ultrasound signal based on a model of sound propagation in soft tissues. More specifically, we treat the ultrasound confidence maps as a new modality to design a visual servoing control law for image quality optimization. The proposed framework aims at improving ultrasound imaging techniques, such as robotic tele-echography, target tracking or volume reconstruction. Here we illustrate our approach with the application of robotic tele-echography. Experiments are performed on both an ultrasound examination training phantom and ex vivo tissue samples.
CRIS-Team Scopus Importer:2023-03-08